The Role of Promotion and Brand Image on Purchase Intention Using Online Applications (Case Study at Ayam Kremes Prambanan Restaurant) - lim, marcella; Frenky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether promotion and brand image have a significant effect on purchase intention at Ayam Kremes Prambanan Restaurant. This study uses quantitative data methods and the data source is primary data. The population in this study were Medan people who had bought from Ayam Kremes Prambanan Restaurant, Wahidin Street branch with an unknown number. Using the Hair et al formula, 120 samples were obtained as respondents. Data analysis and testing consists of validity test, reliability test, descriptive statistical test, classical assumption test, multiple regression analysis, partial hypothesis testing (T test) and simultaneously (F test), and coefficient of determination test. The results showed that promotion has a partially significant effect on purchase intention with a t value of 3.421> t table 1.975. Brand image has a partially significant effect on purchase intention with a t value of 7.918> t table 1.975. Promotion and brand image simultaneously have a significant effect on purchase intention with an F value of 106.633> F table 3.05 with a regression coefficient value of 57.6%.